Musical obsessions: Successful treatment with low dose of escitalopram - Aneesh Alexander; Parthasarathy Ramamurthy; Pradeep Thilakan (Annals of Indian Psychiatry, 2019)
Musical obsessions include repeated intrusive musical tunes, lyrics, or songs. In this report, two patients who presented with isolated musical obsessions and responded well to low dose of escitalopram (10 mg/day) are described. Musical obsessions have to be differentiated from musical hallucinations and palinacousis. Attention to psychopathology and associated clinical features are important in differentiating these conditions. Our case studies add to the limited knowledge of this uncommon condition.